Case Report: A Child With Hemophilia A Serves as Donor for Hematopoietic Stem Cell Transplantation to Cure His Brother's Severe Aplastic Anemia - Gabriella Kertész; Krisztián Kállay; Csaba Kassa; Csaba Kassa; Marianna Zombori; Imre Bodó; Csongor Kiss; István Szegedi; Gergely Kriván; Gergely Kriván (Frontiers Media S.A., 2022)
The first-line treatment of severe aplastic anemia is allogeneic hematopoietic stem cell transplantation with a matched sibling donor. However, co-morbidities of the identical donor can make donation difficult. We present a transplantation where in parallel with the patient's conditioning treatment, the preparation of the donor with severe hemophilia A required a special management with perioperative factor VIII substitution. Donation was successful without complications, and 18 months after transplantation, the patient and his donor are well without any long-term sequelae. To our knowledge, this is the first reported succesfull transplantation with hemophilic child serving as a bone marrow donor. The procedure did not mean a significant risk to donor health, so donors with hemophilia should not be excluded from donation.